2021
DOI: 10.1177/23312165211025938
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Computer-Based Auditory Training for Adult Cochlear Implant Users: A Randomized Crossover Study

Abstract: The aim of this study was to assess whether a computer-based speech-in-noise auditory training (AT) program would lead to short- and long-term changes in trained and untrained measures of listening, cognition, and quality of life. A secondary aim was to assess whether directly training the underlying cognitive abilities required for speech perception in noise, using a computer-based visual training (VT) program without the auditory component, would elicit comparable outcomes as the AT program. A randomized cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 80 publications
(116 reference statements)
2
23
1
1
Order By: Relevance
“…With hearing aid users, the RCT of Ferguson et al (2014) showed generalized far transfer improvements for complex measures of cognition that indexed executive processes, such as divided attention and updating working memory (following a phoneme discrimination performance). However, the only other training study for CI that included cognitive measures (Reis et al 2021) also failed to show improvements in cognitive abilities post-training. Failure to observe changes in performance may be related to significant variability in performance or to the sensitivity of the materials used to assess cognition (Heinrich et al 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…With hearing aid users, the RCT of Ferguson et al (2014) showed generalized far transfer improvements for complex measures of cognition that indexed executive processes, such as divided attention and updating working memory (following a phoneme discrimination performance). However, the only other training study for CI that included cognitive measures (Reis et al 2021) also failed to show improvements in cognitive abilities post-training. Failure to observe changes in performance may be related to significant variability in performance or to the sensitivity of the materials used to assess cognition (Heinrich et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Despite insufficient evidence of CI studies, training results are encouraging. On-task learning improvements following AT have been reported by Fu et al (2005), Oba et al (2011), Zhang et al (2012, Lo et al (2015), Schumann et al (2015), Miller et al (2016), Green et al (2019), andReis et al (2021). An important issue in AT concerns the generalization of improvement to untrained materials and real-world listening environments.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In most studies dealing with auditory training, the impact on trained items has been described, but long-term or transfer effects have rarely been reported [Sweetow and Palmer, 2005;Bernstein et al, 2012;Ingvalson and Wong, 2013;Shafiro et al, 2015;Schumann et al, 2016;Green et al, 2019]. These mixed findings may be due to a limited overlap between the training and the untrained tasks, or due to an insufficient duration of the training used [Reis et al, 2021]. However, a combined auditory-cognitive program might have the potential to improve auditory and cognitive skills in CI users as shown in unaided hard-of-hearing adults [Anderson et al, 2013] and in hearing aid users [Sweetow and Sabes, 2006;Ferguson and Henshaw, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…While CI users' brain can learn new modality of hearing after implantation via passive exposure to sound environment, active auditory training has been suggested to maximize CI benefits (Fu et al, 2008 ; Roman et al, 2016 ; Reis et al, 2021 ). Zhao et al provided valuable direction of possibly using music training in CI users, who typically complain difficulty in music perception.…”
mentioning
confidence: 99%